ПРИЧИНИ МОВЛЕННЄВИХ ПОРУШЕНЬ У ДІТЕЙ ДОШКІЛЬНОГО ВІКУ І ОСНОВНІ НАПРЯМКИ КОРЕКЦІЙНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2004)
Scientific research showed, what very often oral of schoolchildren suffer on criticin periods of her development, wich create proposition condition in order to frustration of oral on 1-2 years, on 3 years, on 6-7 years. Large meaning in correction learning nave diagnostic of different oral’s abnormality.